2020
DOI: 10.1136/injuryprev-2020-043788
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for fatal drowning in a Greek region: a retrospective case–control study

Abstract: BackgroundFatal drowning is one of the leading causes of unintentional injury mortality worldwide and a persistent public health concern in Greece. While several pathologic and sociodemographic contributing factors have been previously identified, these have not been extensively investigated in conjunction with the effects of psychoactive substances.MethodsA retrospective case–control study of drowning deaths was conducted in the Greek regions of Northern Greece and Thessaly during a 10-year period. A regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Ischaemic heart disease was identified in five included studies [ 53 , 55 , 85 , 89 , 90 ]. Two studies were from Greece, finding that ischaemic heart disease was present in 87.9% [ 85 ] and 51.8% of drowning deaths, respectively [ 89 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Ischaemic heart disease was identified in five included studies [ 53 , 55 , 85 , 89 , 90 ]. Two studies were from Greece, finding that ischaemic heart disease was present in 87.9% [ 85 ] and 51.8% of drowning deaths, respectively [ 89 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ischaemic heart disease was identified in five included studies [ 53 , 55 , 85 , 89 , 90 ]. Two studies were from Greece, finding that ischaemic heart disease was present in 87.9% [ 85 ] and 51.8% of drowning deaths, respectively [ 89 ]. Two other studies reporting bath-related deaths found that ischaemic heart disease was present in 34.2% of bath-related deaths in Japan [ 53 ] and 73.7% in South Korea [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Certain types of human activities and the territory of their residence (Carvalho, Kennedy, Woodroffe, 2019), migration processes (Pavlidis, Karakasi, 2019), festive periods such as public holidays (Saunders, Adriaanse, Simons, Niekerk, 2018) have an impact on increasing the number of cases of drowning. Male sex, older age, foreign nationality, and cardiovascular disease predisposed individuals to an elevated risk of fatal submersion (Kevrekidis et al, 2020).…”
Section: Introductionmentioning
confidence: 99%